A Comparative Study of Chinese Homographs in the HSK Level 5 Test - Sangthong, Chalothorn; Nuritamon, Sasithorn (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2025)
This study aims to conduct a comparative analysis of the pronunciations, meanings, and parts of speech of Chinese homographs in the HSK Level 5 Sample Test. The findings from the data analysis reveal that a total of 310 homographic characters appear in the HSK Level 5 Sample Test. Regarding pronunciations, Chinese homographs can be classified into four patterns, with the majority 83.87% being characters that have two possible pronunciations. In terms of meaning, Chinese homographs can be divided into two categories, with those that change meaning being the most common 92.90%. As for parts of speech, they can also be classified into two types, with the largest proportion 70.65% being characters whose parts of speech change. The results of this study indicate that: A significant number of Chinese homographs are included in the HSK Level 5 Sample Test. Encountering such homographs during the exam can easily cause confusion, leading to misreading and potentially reducing test performance. Therefore, strategies for effectively learning, memorizing, and understanding Chinese homographs before the exam include: 1) Recognizing that Chinese homographs often differ in pronunciations, and most of the time their meanings also differ. 2) Understanding that the part of speech of a homograph often reflects its meaning. 3) Some Chinese homonyms may have the same meaning. 4) Focusing on memorizing only the most frequently encountered pronunciations of polyphonic characters to reduce the cognitive load of vocabulary memorization. 5) Paying close attention to the context in which a homograph appears in order to determine its correct pronunciation.